UV Spectrophotometric Estimation of Levoceterizine Dihydrochloride in Bulk and Dosage Form - P. Mamatha; P. V. Anantha Lakshmi; P. L. Prasunamba (E-Journal of Chemistry)
A new simple, rapid, accurate, sensitive and precise spectrophotometric method in ultra violet region has been developed for the determination of levoceterizine dihydrochloride (LCTZ) in bulk drug and tablet dosage form. Levoceterizine dihydrochloride exhibited maximum absorbance at 232 nm with apparent molar absorptivity of 1.5104×104 in double distilled water. Beer's law was found to be obeyed in the concentration range of 4-20 µg mL-1. Correlation coefficient was found to be 0.9998. Results of the analysis were validated statistically and by recovery studies. The proposed method is useful for the routine estimation of LCTZ in bulk and tablet dosage form.